Inhibition of STAT3 prevents bone metastatic progression of prostate cancer in vivo. Issue 8 (6th April 2021) - Thulin, Malin Hagberg; Määttä, Jorma; Linder, Anna; Sterbova, Simona; Ohlsson, Claes; Damber, Jan‐Erik; Widmark, Anders; Persson, Emma
Abstract: Background: Prostate cancer (PC) metastasizes to the skeleton forming predominantly sclerotic lesions, and there is currently no cure for bone metastatic disease. The transcription factor signal transducer and activator of transcription 3 (STAT3) is implicated as a metastatic driver, but its potential as therapeutic target in bone metastasis has not been investigated. In this study, we evaluated for the first time a STAT3 inhibitor, Napabucasin, as a therapeutic option for bone metastatic PC. Methods: Effects of STAT3 inhibitors, Stattic and Napabucasin, on metastatic potential in PC cells were studied in vitro by assessment of migration capacity, self‐renewal potential, and tumorsphere formation. For evaluation of the role of STAT3 in initial skeletal establishment of PC cells as well as in progressed castration‐resistant PC (CRPC) in bone, human VCaP prostate cancer cells were inoculated in the tibia of mice which subsequently were treated with the STAT3 inhibitor Napabucasin. Bone specimens were analyzed using computed tomography (CT), immunohistochemistry, and quantitative polymerase chain reaction. Results: The small molecule STAT3 inhibitors Stattic and Napabucasin both effectively impaired metastatic potential of PC cells in vitro. Furthermore, treatment with Napabucasin prevented metastatic establishment in tibial bones in vivo and thereby also the tumor‐induced sclerotic bone response seen in vehicle‐treated VCaP xenografts. In addition, treatment with Napabucasin of established bone CRPC significantly decreased both tumor burden and tumor‐induced trabecular bone volume compared with effects seen in vehicle‐treated animals. Anti‐mitotic effects were confirmed by decreased Ki67 staining in Napabucasin‐treated xenografts compared with vehicle‐treated xenografts. Alterations of gene expression in the femoral bone marrow (BM) niche toward the maintenance of hematopoietic stem cells and the myeloid lineage were demonstrated by quantitative real‐time polymerase chain reaction and were further reflected by a substantial increase in the number of erythrocytes in BM of Napabucasin‐treated mice. Furthermore, a unique pattern of STAT3 phosphorylation in osteoblasts/stromal cells surrounding the areas of tumor cells was demonstrated immunohistochemically in bone xenograft models using several different PC cell lines. Conclusion: Inhibition of STAT3 activity disrupts the bone metastatic niche and targets both the skeletal establishment of PC and advanced bone metastatic CRPC in mice, suggesting STAT3 as a candidate for molecular targeted therapies of skeletal metastatic disease.